2015
DOI: 10.1021/acs.organomet.5b00448
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Investigation of a Parallel Catalytic Cycle in CO2 Hydrogenation by (PNP)IrH3

Abstract: The (PNP)IrH 3 (2,6-bis(diisopropylphosphinomethyl)pyridine iridium trihydride) complex by Nozaki is a highly active and selective catalyst for CO 2 hydrogenation to formic acid in aqueous KOH. Previous theoretical investigations found that regeneration of the catalyst is the rate-determining step in this reaction. In the current article we present results from a computational study using density functional theory in order to consider the possibility of sequential insertion of two CO 2 molecules in two Ir−H bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 66 publications
(48 reference statements)
0
25
0
Order By: Relevance
“…Considering the fact that an aqueous basic medium (NaOH aq.) is required to produce formate, the produced formate ion is displaced by hydrogen to afford a cationic intermediate Ir species (Step 4), which is subsequently deprotonated in the basic reaction medium to regenerate the initial active species (Step 5) . The produced formate is considered to be stabilized either by forming sodium formate (HCOONa) with Na + ions existing in the reaction medium or by adsorption onto the basic sites of PEI and TNT surface, thereby enabling the continuous production of formate over the present catalytic system.…”
Section: Resultsmentioning
confidence: 99%
“…Considering the fact that an aqueous basic medium (NaOH aq.) is required to produce formate, the produced formate ion is displaced by hydrogen to afford a cationic intermediate Ir species (Step 4), which is subsequently deprotonated in the basic reaction medium to regenerate the initial active species (Step 5) . The produced formate is considered to be stabilized either by forming sodium formate (HCOONa) with Na + ions existing in the reaction medium or by adsorption onto the basic sites of PEI and TNT surface, thereby enabling the continuous production of formate over the present catalytic system.…”
Section: Resultsmentioning
confidence: 99%
“…To date, the most promising homogeneous hydrogenation pincer catalysts consist of transition metal complexes (e.g., Ir, Rh, Ru, and Fe) incorporating PNP pincer ligands based on a 2,6-dimethylpyridine scaffold where the P and N atoms are directly bound to the metal center. The connecting atoms of the pincer backbone can be swapped with either N or C, which leads to a host of different ligand families (e.g., PNN, NNN, PCP), as illustrated in Figure b. Perhaps the most well-known homogeneous catalytic system for the hydrogenation of CO 2 to formate used a Ir III –PNP catalyst (PNP = 2,6-bis­(diiso­propyl­phosphino­methyl)­pyridine) and yielded a maximum turnover number of 3500000. , Subsequent experimental and theoretical investigations have also revealed that this, as well as other metal–pincer complexes, should be capable of catalyzing the hydrogenation reaction. Nevertheless, despite considerable experimental and computational work, a comprehensive picture on why certain metal/ligand combinations are superior to others is currently lacking.…”
Section: Introductionmentioning
confidence: 99%
“…In the present case, our work presented that not only the nature of Ru-H bond correlates with the hydride transferring process, but also the trans ligand of hydride relates to catalytic activity in the whole pathway for the hydrogenation of CO2 to formate. Furthermore, some study 49 demonstrated that the process of CO2 insertion into Ru-H bond via direct hydride abstraction pathway is a sequentially uphill step. Therefore, the whole process of hydrogenation of CO2 to formate should be paid attention and the overall barriers are used to measure the catalytic efficiency of these complexes.…”
Section: Hydrogenation Process Of Co2 To Formate Onmentioning
confidence: 99%